2007
DOI: 10.1142/s0129183107011868
|View full text |Cite
|
Sign up to set email alerts
|

Implicit-Explicit Finite-Difference Lattice Boltzmann Method for Compressible Flows

Abstract: We propose an implicit-explicit finite-difference lattice Boltzmann method for compressible flows in this work. The implicit-explicit Runge–Kutta scheme, which solves the relaxation term of the discrete velocity Boltzmann equation implicitly and other terms explicitly, is adopted for the time discretization. Owing to the characteristic of the collision invariants in the lattice Boltzmann method, the implicitness can be completely eliminated, and thus no iteration is needed in practice. In this fashion, problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 42 publications
0
55
0
1
Order By: Relevance
“…For the implementation of the advection term, we use a 5th order WENO scheme [21]. It was shown that the WENO scheme is suitable when simulating flows with discontinuities or strong gradients, in effect suppressing spurious oscillations and reducing numerical viscosity [20].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For the implementation of the advection term, we use a 5th order WENO scheme [21]. It was shown that the WENO scheme is suitable when simulating flows with discontinuities or strong gradients, in effect suppressing spurious oscillations and reducing numerical viscosity [20].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Of course, in reality there is no fluid or flow that is absolutely incompressible (i.e., with infinite acoustic velocity). Recent works have shown that it is possible to define lattices able to overcome this limitation (see, for instance, [8], where the authors lay the theoretical foundation of the lattice Boltzmann model for the simulation of flows with shock waves and contact discontinuities, also [9], where one can find a powerful scheme the computational convergence rate of which can be improved compared to classical previous ones, while proving to be efficient for Taylor vortex flow, Couette flow, Riemann problem).…”
Section: Introductionmentioning
confidence: 99%
“…Since the LBM can be regarded as a discrete velocity method for the Boltzmann equation with the BGK approximation, it is not surprising that there is a trend in the LBM world to use the finite-difference method [16,17,23,[25][26][27][28][29][30][31][32][33][34], the finite-volume method [24,[35][36][37][38] and the finite-element method [39] to improve the computational efficiency and accuracy. In the finite-difference LBM (FDLBM), the streaming-collision procedure in the standard LBM is replaced by the combination of finitedifference schemes for the convection term in the Boltzmann equation and step advancements in time.…”
Section: Introductionmentioning
confidence: 99%